Imunoexpressão de Caderina-E no câncer colorretal primário e nas metástases linfonodais - Sampaio, João Paulo Aguiar (2013)
E-cadherin is closely related to epitelial-mesenchymal transition and tumor progression in many cancers, including colorectal cancer. The aim of this study is to evaluate the expression of E-cadherin in primary colorectal cancer as well as in lymph node metastasis, establishing also a comparison with the expression of E-cadherin in normal colonic mucosa. We utilized 77 cases of colectomies for colorectal carcinoma and 10 cases of metastatic lymph nodes from the files of the Department of Pathology and Forensic Medicine/Federal University of Ceara. Tissue microarray and immunohistochemistry were performed with monoclonal anti-E-cadherin, evaluated using the following scores: 0 = no staining; 1 = cytoplasmic staining; 2 = mixed staining (cytoplasmic and membranous); 3 = membranous staining. It was used the classification proposed by Jawahri et al. which includes cases of abnormal expression (0, 1 and 2 scores) and cases of normal expression (3 score), and was also used the classification proposed by Almeida et al. which includes cases of non-membranous expression (0 and 1 scores) and membranous expression (2 and 3 scores). Primary tumors presented more cases of abnormal E-cadherin expression in comparison to normal colonic mucosa (p < 0.0001). There were no differences between E-cadherin expression in the primary tumor in comparison to lymph node metastasis. The grouped cell tumors showed increased expression of E-cadherin in comparison to isolated cell tumors, either using the classification proposed by Jawhari et al. (p = 0.0230) and the classification proposed by Almeida et al. (p = 0.0043). In conclusion, abnormal expression of E-cadherin in the primary tumor, with frequent membranar immunostaining associated with the cytoplasmic marking (abnormal heterogeneous or mixed staining), reinforces the evidence that E-cadherin expression change in cancer is more qualitative than quantitative. The predominance of membranar expression in primary tumor and lymph node metastasis, with or without associated cytoplasmatic expression, particularly in cell-grouped tumors, suggests that E-cadherin presence is essential for local invasion and tumor progression, as opposed to the classical paradigm that tumor progression is exacerbated by the loss of this adhesion molecule.